HUBUNGAN ORAL HIGIENE INDEX (OHI) DENGAN PROBING POCKET DEPTH (PPD) DAN LOSS OF ATTACHMENT (LOA) PADA LANJUT USIA - Kriswiharsi Kun Saptorini (VISIKES: Jurnal Kesehatan Masyarakat, 2011)
Periodontal disease is an inflammation of the gingival tissues supporting the teeth, periodontal ligament, cementum and alveolar bone. Risk factors include age, gender, oral hygiene,the number of remaining teeth, smoking, knowledge, attitudes, practices in relation to periodontal status assessed by Probing Pocket Depth and Loss of Attachment has not been widely studied. Purpose of this study to prove association between oral hygiene with Probing Pocket Depth and Loss of Attachment.This study is an observational research with cross sectional design. The population study was the elderly aged eâ€ 60 years old enrolled in the 5 Posyandu lansia in Wonosari area, with a sample size of 72 people. The data was collected by interview, clinical observation and focus groups discuss. Data were analyzed with chi square test.The results showed that Oral Hygiene Index (OHI) showed a significant association with Probing Pocket Depth (PPD) with p-value = 0,036, 95% CI = 1,199 to 9,110, PR = 3,306. Oral Hygiene Index (OHI) showed a significant association with the Loss of attachment (LOA) with p-value = 0,028, 95% CI = 1,207 to 80,367, PR = 9,848.The conclusions of this study, that poor Oral Hygiene Index (OHI) had a 3,3 times risk of having poor Probing Pocket Depth (PPD) and poor Oral Hygiene Index (OHI) had a 9,8times risk of having poor Loss of Attachment (LOA).Based on the results, it is recommended that the elderly need to maintain teeth at least 20 teeth and need to do scaling, scaling is also included in ASKES / Jamkesmas, cooperation with the private sector in public education activities and community service in the form of dental health checks and consultations are needed.Keywords : elderly, periodontal status, risk factors.